Proceedings of the 2000 ACM Conference on Computer Supported Cooperative Work 2000
DOI: 10.1145/358916.358978
|View full text |Cite
|
Sign up to set email alerts
|

Providing presence cues to telephone users

Abstract: A significant problem with telephone communication is that callers do not have enough awareness about the Personal Presence of people they want to call. The result can be unwanted, interrupting calls. The live addressbook is an application that helps users make more informed telephone calls and teleconferences, from anywhere, via their wireless PDA or desktop browser. Unlike other network-based address books, which maintain static information, the live addressbook can display dynamic information about where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 13 publications
3
85
0
1
Order By: Relevance
“…While users can characterize their own interruptibility preferences by changing phone modes (e.g., ring, vibrate, silent) to avoid unwanted phone calls [27], they often forget to set and reset their phone modes, resulting in unwanted interruptions or potentially missing important calls, or SMS or calendar notifications due to silent notifications [21]. With a model of interruptibility, a phone could automatically set its volume to avoid inappropriate interruptions and important missed calls.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…While users can characterize their own interruptibility preferences by changing phone modes (e.g., ring, vibrate, silent) to avoid unwanted phone calls [27], they often forget to set and reset their phone modes, resulting in unwanted interruptions or potentially missing important calls, or SMS or calendar notifications due to silent notifications [21]. With a model of interruptibility, a phone could automatically set its volume to avoid inappropriate interruptions and important missed calls.…”
Section: Related Workmentioning
confidence: 99%
“…While we receive reminders to turn off our phones or put them in silent mode in these contexts, we often forget to do so which can result in embarrassing situations. Even when we do remember, we then forget to turn the ringer on afterwards resulting in missed calls [21] or missed notifications about SMS messages and calendar events. In this work, we are interested in learning users' preferences for receiving audible notification preferences in order to enable an application we built to automatically change the volume of users' phones.…”
Section: Introductionmentioning
confidence: 99%
“…Instant Messaging (IM), in contrast, has become of great interest to the CSCW community because it is a tool that successfully supports informal communication [5,6,13,14]. Nardi et al [14], for example, reported cases where IM was preferred to informal FTF conversation because it is less intrusive and allows multitasking.…”
Section: Introductionmentioning
confidence: 99%
“…Most of our initial understanding of the use of instant messaging comes from self-reports, primarily interview studies [3,5,6,13,14] or marketing surveys [12,15,16]. While helpful for getting a sense of IM practices, these studies usually have been based on relatively small sets of users and little direct observation of instant messaging activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation